Electrical characteristics of bismuth titanate glass-ceramics containing SiO2 and Nd2O3 - Stanislav S. Slavov; Milena Z. Krapchanska; Elena P. Kashchieva; Yanko B. Dimitriev (Processing and Application of Ceramics, 2010)
Bismuth-titanate ceramics containing SiO2 and Nd2O3 as additives are synthesized at two different ways of cooling of the melts. The introduction of SiO2 and Nd2O3 leads to more complex crystallization with participation of several phases including Bi4Ti3O12. It is proved that the applied methods of synthesis are suitable for generation of different microstructures in the bulk doped bismuth titanate ceramics, which is promising basis for modification of their electrical properties. The increasing of SiO2 content improves the glass formation ability and addition of Nd2O3 stimulates the crystallization. The conductivity of selected samples is determined by impedance analyzer in the frequency range from 10 to 100 kHz and DC resistible bridge using two-terminal method. All investigated samples are dielectrics with conductivity 10-6–10-9 (Ω·cm)-1.